2019
DOI: 10.3390/e21090830
|View full text |Cite
|
Sign up to set email alerts
|

A New Physically Meaningful Threshold of Sample Entropy for Detecting Cardiovascular Diseases

Abstract: Sample Entropy (SampEn) is a popular method for assessing the regularity of physiological signals. Prior to the entropy calculation, certain common parameters need to be initialized: Embedding dimension m, tolerance threshold r and time series length N. Nevertheless, the determination of these parameters is usually based on expert experience. Improper assignments of these parameters tend to bring invalid values, inconsistency and low statistical significance in entropy calculation. In this study, we proposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Thus, we tested the effects of different values of etc., and found that provided the best discrimination between the CHF and NSR groups. In this study, we used the previously proposed fixed tolerance method with [ 26 ] with physical meaning to analyze the RR interval time series with ectopic beats, to explore if the new method has better performance for ectopic time series. Forty-five NSR and 24 CHF recordings were enrolled in this study, all of which had an appreciable number of ectopic beats, including atrial and ventricular beats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we tested the effects of different values of etc., and found that provided the best discrimination between the CHF and NSR groups. In this study, we used the previously proposed fixed tolerance method with [ 26 ] with physical meaning to analyze the RR interval time series with ectopic beats, to explore if the new method has better performance for ectopic time series. Forty-five NSR and 24 CHF recordings were enrolled in this study, all of which had an appreciable number of ectopic beats, including atrial and ventricular beats.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite entropy change trend brings difficulty to defining a unified threshold to distinguish CHF patients from NSR subjects in heart rate variability (HRV) analysis. To solve this problem, we proposed a physical threshold-based SampEn method to discriminate the opposite entropy change trend in the task of classifying CHF and NSR subjects [ 26 ], where the physical threshold-based SampEn was demonstrated to have a better stability than the traditional SampEn.…”
Section: Introductionmentioning
confidence: 99%
“…The inverted entropy results make it hard to establish a unified standard to detect CHF subjects with a constant r value. To avoid such inconsistency, we proposed a physical threshold as multiple of sampling period, and proved that it is more adaptive to CHF detection than the traditional threshold [ 29 ]. Since the signals were sampled at 128 Hz, we regarded sampling period as 8 ms, and set threshold r as 1.5 times the sampling period, which equals to 12 ms.…”
Section: Methodsmentioning
confidence: 99%
“…In previous study [ 29 ], we used physical threshold-based SampEn to distinguish CHF subjects from NSR subjects. As the results have shown, the average SampEn values of CHF group are significantly lower than those of NSR group when using m = 1, 2 and N = 300, 1000, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation